Industrial attachment report with Micron Semiconductor Asia Pte Ltd - Airin Alamsjah (2008)
Two projects were performed: (1) involves verification of PBGA solder ball shear strength trend in terms of 2 pads designs, Solder Mask Defined and Non-Solder Mask Defined; (2) focus on module level reliability check out.